Um sítio arqueológico, vários museus: o caso do Engenho do Murutucu, Belém/PA - SANTOS, Sabrina Fernandes dos (2019)
This article discuss how New Museology and Public Archaeology deal with a shared management of cultural heritage. We use a historical archaeological site, called Murutucu sugar cane mil, as case study to demonstrate the difference between meanings attributed to the patrimony; from the perspective of the public who visited this space during educational activities occurred in July of 2015. The results from oral interviews presented themes to discuss the safeguard policies, as well as,meanings attributed to cultural and archaeological heritage by the contemporary societies.